Short Stories, a Didactic Resource in the Teaching of French as a Second Language, - Sonia Rut Badenas Roig (Revista de Lingüística y Lenguas Aplicadas)
This article offers a pragmatic reflection on the use of short stories in the teaching of French as a foreign language. After analyzing the use of short stories in the foreign language classroom as didactic material, we briefly assess the different advantages of short stories and inquire about the validity of this genre as a suitable material for the teaching of written expression in the light of the Common European Framework of Reference for Languages (CEFRL). On this basis, we propose a practical approach in which short stories are integrated to the teaching of written expression within a communicative context.